Risk and protective factors influencing educational success and suicidality for First Nations youth-in-care in Ontario, Canada - Greenberg, Barbara; Miller, Meagan; Michael, Erik; Flynn, Robert J. (Université d'Ottawa | University of Ottawa, 2016)
Presented at the XIVth European Scientific Association on Residential and Family Care for Children and Adolescents (EUSARF) international conference in Oviedo, Spain in September, 2016
Keywords: First Nations; Indigenous; Indigenous youth; child welfare; education; suicide; youth-in-care; youth